MO868CLINICAL OUTCOMES FOR INTRAVENOUS DRUG USERS REQUIRING HAEMODIALYSIS. (29th May 2021) - Burns, Katy; Kanigicherla, Durga; Hamilton, Patrick
Abstract: Background and Aims: Intravenous drug users (IVDU) face significant challenges when requiring long-term therapies such as dialysis and pose management dilemma to clinicians. Many patients present late, complicated by erratic lifestyles and complex mental health needs, often requiring urgent renal replacement therapy (RRT). Decisions regarding modality can be difficult due to the lack of evidence for outcomes in this cohort. We investigated the clinical outcomes of patients with history of IVDU in our service who presented with ESRD. Method: A single-centre retrospective analysis of ESRD patients with a background of IVDU. Incidence of hospital and ICU admission, length of stay and frequency of culture positive sepsis following the initiation of RRT were investigated. Primary outcome was days admitted versus days spent in the community, frequency of life-threatening sepsis and tunnelled catheter replacement. Data was collected from the date of first RRT (earliest April 2015 and latest November 2019) to last follow-up in September 2020 or patient death. An admission was included when the patient was admitted for at least an overnight stay in hospital. Admission days calculated do not include attendance for outpatient haemodialysis. Bacteraemia's were included when a report confirming a positive culture associated with clinical features of infection; paired samples were counted as a single episode. Results: Six patients initiated RRT during the study period and included four males and two females. Mean age of 46.6 years (32-54 years). Cause of ESRD was Amyloid AA in 5) and IgA nephropathy in 1). Mean follow-up was 677 days till censor (range 313 to 932 days). There was an average of nine inpatient admissions (range 3 to 17) averaging 280 inpatient days (range 29 to 637 days) across the cohort. At last follow-up, three patients died with an average time to death of 833 days from initiation of RRT (range 664 to 932 days). Four patients required at least one admission to the Intensive Care Unit (ITU) with an average length of stay of 10.3 days (range 1 to 47 days). All patients experienced at least two episodes of culture positive sepsis with a total of 72 bacteraemia's across the cohort (range 2 to 41). Four patients required tunnelled catheter replacement ranging from 2 to 7 catheters. Results are summarised in Table 1 . Conclusion: IVDU patients represent a challenging patient population to manage with limited options available for RRT. This study highlights these difficulties particularly with the use of tunnelled catheters for haemodialysis. Our results indicate RRT in IVDUs is associated with frequent and prolonged hospital stays with multiple bacteraemia's, ICU admissions and significant mortality. Clinicians are faced with a significant ethical dilemma as tunnelled catheters represent both a lifeline for continued survival and a perfect access to recreational drugs. If patients are to be offered haemodialysis via tunnelled access, more intensive and earlier multidisciplinary planning and counselling needs to be employed to ensure patients are aware of the significance of the associated risks. Psychological therapy and social care input would be essential to help reduce morbidity and mortality.